Perbandingan Perencanaan Tebal Perkerasan Lentur dengan MDP 2024 dan Plaxis 3D Foundation pada Timbunan di Atas Tanah Clay Shale - Intan Erika Permata Sari; Murniati; Robby (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Clay shale is a type of clay soil formed by fine-grained sediments such as clay. Clay shale is very hard under closed conditions, but under open conditions, exposed to sunlight, water and air for a long time, its state changes and becomes weak, which ultimately causes a decrease in soil shear strength. The purpose of this thickness comparison is to analyze the feasibility of clay shale soil as a base layer for highway pavement with the thickness of MDP 2024. The analysis results show that the deflection and stress that occur in the flexible pavement structure are both safe/feasible. Thus, both pavement thicknesses can be implemented. The results of stress and deflection from IKN design data are the maximum stress of 823.2 kN/m2 < 1,450 kN/m2 (allowable stress) and 2.668 x 10-3 m < 2.5 10-2 m (allowable deflection). As for the results of stress and deflection with thickness The 2024 Road Pavement Design Manual method is used, the maximum stress is 1075 kN/m2 < 1,450 kN/m2 (allowable stress) and 1,601 x 10-3 m < 2.5 10-2 m (allowable deflection). It is recommended to use the design pavement thickness from the IKN design for the evaluation because the stability of the flexible pavement structure in the IKN design is better than the pavement structure using the MDP 2024 method.